If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7x + -1 = 4x + -3 Reorder the terms: -1 + 7x = 4x + -3 Reorder the terms: -1 + 7x = -3 + 4x Solving -1 + 7x = -3 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. -1 + 7x + -4x = -3 + 4x + -4x Combine like terms: 7x + -4x = 3x -1 + 3x = -3 + 4x + -4x Combine like terms: 4x + -4x = 0 -1 + 3x = -3 + 0 -1 + 3x = -3 Add '1' to each side of the equation. -1 + 1 + 3x = -3 + 1 Combine like terms: -1 + 1 = 0 0 + 3x = -3 + 1 3x = -3 + 1 Combine like terms: -3 + 1 = -2 3x = -2 Divide each side by '3'. x = -0.6666666667 Simplifying x = -0.6666666667
| 4x+0.2=6.6 | | 5x+4-4x=12-29 | | n^2-n+4=0 | | 5x-11-4x=-5 | | p=4n-50 | | 6k^2+22k-8=0 | | (x+2)(x+5)=-2 | | 4w+12w-10=16w-10 | | (6+4)*2-7+9+18+(5+1*3)+5=688 | | 3(0.6+2n)-3.2=7.6 | | x(x-5)=x^2+3x+5 | | 4x+13x=102 | | x^4-9= | | (6+4)*2-7+9+18+(5+1*3)+5=x | | 2x^2=-9x | | 90x^2+1=6x | | 2.5d=0.4f+50 | | -72x^4-8x^3= | | 3(k+5)=-19 | | 15x^2-26x+8=0 | | x+9=-5x+9 | | 8y-4=3y+6 | | 8(x-8)+x=9(x-8)+8 | | (6+4)*2-7+9+18+(5+1*3)+5= | | 18x^2-50=0 | | 23x+5=15+3x | | 4(5c-1)-4=15c+7 | | 2t-8=3(t+5) | | 6n^2-21n=0 | | 3x+2x=125 | | 4(x+8)+x=-9(4-x) | | 32+2y-8=9y-11-2y |